The Development of an AI-Scratch Interactive Learning Model for Elementary Art Education - Teguh Iman Perdana Surbakti; Siti Aisyah; Safitri Yosita Ratri (Gorga : Jurnal Seni Rupa, 2026)
This study sought to develop and assess an AI-Scratch interactive learning model for elementary visual art education at SD HighScope Indonesia Medan. The research was motivated by the limited integration of interactive digital media in visual art learning, which remained predominantly focused on conventional drawing activities and teacher-centered instruction. The study employed a mixed-method Research and Development (R&D) approach adapted from the Borg and Gall model, comprising needs analysis, model development, expert validation, revision, classroom implementation, and effectiveness evaluation stages. The developed model integrated Scratch-based animated digital comic activities with adaptive AI-supported interaction to facilitate visual storytelling, creative exploration, and interactive learning experiences. The findings indicated that the developed learning model met instructional feasibility criteria based on material expert and media expert validation results. The implementation of the AI-Scratch learning model significantly enhanced students’ learning outcomes, as evidenced by the increase in the average pretest score from 61.42 to the average posttest score of 81.38. Statistical analysis employing paired sample t-test revealed significant differences between pretest and posttest results, while the average N-Gain score of 0.554 indicated moderate learning improvement. Furthermore, the calculated effect size value of 1.96 demonstrated a substantial instructional impact. The results also revealed positive development in students’ creativity across fluency, flexibility, originality, and elaboration dimensions during animated digital comic creation activities. In summary, the AI-Scratch interactive learning model contributed to the development of adaptive, creativity-oriented, and visually interactive learning innovation in elementary visual art education.